An increase in surface hydrophobicity mediates chaperone activity in N-chlorinated RidA - Varatnitskaya, Marharyta; Fasel, Julia; Müller, Alexandra; Lupilov, Natalie; Shi, Yunlong; Fuchs, Kristin; Krewing, Marco; Jung, Christoph; Jacob, Timo; Sitek, Barbara; Bandow, Julia E.; Carroll, Kate S.; et al. (Redox biology, 2022)
Under physiological conditions, Escherichia coli RidA is an enamine/imine deaminase, which promotes the release of ammonia from reactive enamine/imine intermediates. However, when modified by hypochlorous acid (HOCl), it turns into a potent chaperone-like holdase that can effectively protect E. coli's proteome during oxidative stress. However, it is unknown, which residues need to be chlorinated for activation. Here, we employ a combination of LC-MS/MS analysis, a chemo-proteomic approach, and a mutagenesis study to identify residues responsible for RidA's chaperone-like function. Through LC-MS/MS of digested RidAHOCl, we obtained direct evidence of the chlorination of one arginine residue. To overcome the instability of the N-chloramine modification, we established a chemoproteomic approach using 5-(dimethylamino) naphthalene-1-sulfinic acid (DANSO2H) as a probe to label N-chlorinated lysines. Using this probe, we were able to detect the N-chlorination of six additional lysine residues. Moreover, using a mutagenesis study to genetically probe the role of single arginine and lysine residues, we found that the removal of arginines R105 and/or R128 led to a substantial reduction of RidAHOCl's chaperone activity. These results, together with structural analysis, confirm that the chaperone activity of RidA is concomitant with the loss of positive charges on the protein surface, leading to an increased overall protein hydrophobicity. Molecular modelling of RidAHOCl and the rational design of a RidA variant that shows chaperone activity even in the absence of HOCl further supports our hypothesis. Our data provide a molecular mechanism for HOCl-mediated chaperone activity found in RidA and a growing number of other HOCl-activated chaperones.